(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article talks about Alisher Navoi’s 7-verse ghazal becoming a 9-verse ghazal in the process of editing "Badoyi’ul-Bidaya" and later "Khazayin ul-Maoni". For this purpose, the text of the seven-verse ghazal "Badayi’ ul-bidaya" beginning with the line "Ochib koksum shikofin, ayladim konglumni nazzora" is in "Badayi’ ul-wasat" which consists of nine verses of this ghazal. with the text is studied in a historical-comparative method, attention is paid to the fact that the textual differences are the result of the author’s editing. Alisher Navoi’s "Garayib us-sigar" "Debocha" is based on the poet’s other works and comments on the author’s editing recognized by our literary experts. It is revealed on the basis of analysis that it created an opportunity for the poet. Also, in the edited text of the ghazal, there is an opinion about the omission of four stanzas from the original text.